Proceedings of the 17th ACM Great Lakes Symposium on VLSI 2007
DOI: 10.1145/1228784.1228833
|View full text |Cite
|
Sign up to set email alerts
|

Novel architectures for efficient (m, n) parallel counters

Abstract: Parallel counters are key elements in many arithmetic circuits, especially fast multipliers. In this paper, novel architectures and designs for high speed, low power (3, 2), (7, 3), (15, 4) and (31,5) counters capable of operating at ultra-low voltages are presented. Based on these counters, a generalized architecture is derived for large (m, n) parallel counters. The proposed architecture lays emphasis on the use of multiplexers and a combination of CMOS and transmission gate logic in arithmetic circuits that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…This conclusion is also emphasized by [14] since the Dada tree is optimum in providing the minimum number of full adders. Dadda showed that the approach can also work for larger adders such as the (7,3) and (15,4). The performance of Wallace and Dadda trees is very similar in terms of delay and power.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion is also emphasized by [14] since the Dada tree is optimum in providing the minimum number of full adders. Dadda showed that the approach can also work for larger adders such as the (7,3) and (15,4). The performance of Wallace and Dadda trees is very similar in terms of delay and power.…”
Section: Related Workmentioning
confidence: 99%
“…And it cannot produce an all 1s output combination (111) 2 = 7 while a (7,3) counter is saturated. There has been a lot of work on counter design such as in [15,16] to design low power and provide fast counters.…”
Section: Counters and Compressorsmentioning
confidence: 99%
“…(n+1)) parallel counter that counts the number of logic '1's in an n-bit input and yields Parallel counters are commonly used in fast Optimized CMOS counter have been shown in [15] for and the design complexity has been number of logic gates needed. Designing these gates with WHFM provides a 2X performance gain per unit gate delay.…”
Section: Projected Benefits Over State-of-the-art Scaled Cmos: Inmentioning
confidence: 99%
“…The WHFM implementation requires only 3 logic devices, as opposed to 12 logic gates needed for an optimized CMOS (7, 3) parallel counter [15]. Table II shows how logic complexity scales for WHFM and CMOS versions of the parallel counter.…”
Section: Projected Benefits Over State-of-the-art Scaled Cmos: Inmentioning
confidence: 99%
See 1 more Smart Citation